Medical thoracoscopic photodynamic therapy for metastatic pleural tumors with malignant effusion: an exploratory pilot study - Mai, Zhonglun; He, Qianwen; Tang, Yao; Feng, Qixiao; Wu, Ziqing (Frontiers in Oncology, 2025)
BackgroundThe optimal treatment for malignant pleural effusion (MPE) remains controversial. We previously explored the use of minimally invasive medical thoracoscopic thermal ablation [argon plasma coagulation (APC)] to reduce pleural tumors and manage effusion, achieving encouraging results. However, this method has some drawbacks.MethodsWe conducted an exploratory pilot study to evaluate the efficacy of photodynamic therapy (PDT), alone or in combination with APC, in the treatment of pleural spread with MPE. Patients with plaque-like lesions received PDT alone with an energy density of 384 J/cm2. Nodular-like and mass-like lesions were treated with APC followed by PDT with energy densities of 480 and 576 J/cm2, respectively. The primary endpoints were the response and time to progression (TTP). The 1-year survival rate and safety were also assessed. Data from the PDT ± APC group were compared with those from the APC group from our previous study.ResultsIn total, 28 patients with non-small lung cancer (NSCLC) were enrolled. Eight patients underwent PDT alone and 20 patients underwent PDT and APC. At week 6, the overall response rate in the observation group was 82.1% (complete response in 15 cases and partial response in eight cases). At week 12, this rate had increased to 89.3%. The TTP was significantly longer in the PDT ± APC group than in the APC group (median, 20.7 vs. 14.2 months; P = 0.006; HR = 0.35). The 1-year survival rate was 75% (21/28).ConclusionMedical thoracoscopic PDT ± APC therapy significantly improved TTP relative to APC alone and provided durable local effusion control among NSCLC patients with MPE.